Manganese transport disorder: Novel SLC30A10 mutations and early phenotypes. Issue 7 (17th March 2015) - Quadri, Marialuisa; Kamate, Mahesh; Sharma, Suvasini; Olgiati, Simone; Graafland, Josja; Breedveld, Guido J.; Kori, Indu; Hattiholi, Virupaxi; Jain, Puneet; Aneja, Satinder; Kumar, Atin; Gulati, Parveen; et al.
ABSTRACT Background SLC30A10 mutations cause an autosomal recessive disorder, characterized by hypermanganesaemia, polycythemia, early‐onset dystonia, paraparesis, or late‐onset parkinsonism, and chronic liver disease. This is the first identified inborn error of Mn metabolism in humans, reported in 10 families thus far. Methods Methods for this study consisted of clinical examination, neuroimaging studies (MRI), serum dosages, and SLC30A10 genetic analysis. Results We describe early disease manifestations (including videos) in 5 previously unreported Indian children, carrying novel homozygous SLC30A10 mutations. Gait and speech disturbances, falls, dystonias, and central hypotonia were the presenting neurological features, starting within the first 5 years of life. All children also had severe hypermanganesemia, polycythemia, variable degree of liver disease, and marked brain MRI T1 hyperintensities. Conclusions Our findings expand the mutational and clinical spectra of this recently recognized disorder. An early diagnosis is warranted, because treatment with manganese‐chelating agents, iron supplementation, or their combination might improve symptoms and prevent progression of this otherwise potentially fatal disease. © 2015 International Parkinson and Movement Disorder Society